New design chart for CFRP strengthened RC walls with opening in one-way action. (April 2020) - Lima, Mehdi; Doh, Jeung-Hwan; Fragomeni, Sam
Abstract: Reinforced Concrete (RC) walls have been widely used in the construction of medium/high-rise buildings due to their substantial advantages, including fast construction and cost-effectiveness. Nowadays, custom architectural designs have given rise to openings in RC walls for various purposes including doors, windows and vents. Creating such openings within the existing walls alters the ultimate strength of the wall and introduces changes to the intended load path through the element. The situation will become more complex when considering the various support conditions and possible opening configurations. In this research, a comprehensive numerical investigation is completed on Carbon Fibre Reinforced Polymer (CFRP) strengthened RC walls. For the first time, a design chart is proposed for the axial load design of CFRP strengthened RC walls considering two main factors, opening configurations and CFRP layouts. The proposed charts have been verified and validated against existing experimental data and available axial load design formulae. It was found that the proposed design chart can reasonably predict the axial ultimate load capacity of CFRP strengthened RC walls. Step by step instructions are presented to employ these charts and case studies are also provided for clarification and illustration.